The Ideal Pattern of Social Integration Based on the Quran (Thematic Study of Verses on Social Integration) - Asrin; Anshori, Afif; Shonhaji; Mawardi; Imron, Inrawati; Setiawati, Rini (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to explore the ideal concept of social integration patterns based on the Quran through a thematic study of verses related to social integration. In the modern context, social integration often faces challenges such as social inequality, intergroup conflicts, and lack of tolerance. The structural functionalism theory pioneered by Talcott Parsons provides a theoretical basis regarding the importance of balance in society to achieve social order. However, the concept of social integration in Islam emphasizes principles of justice, unity, and tolerance as outlined in the Quranic verses. Verses such as those in Surah Al-Hujurat (49:13) and Surah Al-Maidah (5:2) teach the importance of mutual recognition among nations and tribes, as well as cooperation in righteousness and piety. The Quran also emphasizes the importance of justice (Surah An-Nisa 4:58) and the unity of the ummah (Surah Ali Imran 3:103) as the main foundations for achieving harmonious social integration. This study finds that the ideal pattern of social integration according to the Quran is based on principles of justice, unity, mutual assistance, and recognition of differences, which, if consistently applied, can address various social challenges faced today.